A model of common monetary policy - Juha Tarkka (Bank of Finland, 1997)
This paper analyses the prerequisites for and the results of unanimous monetary policy decisions in a monetary union consisting of heterogeneous members.The analysis is based on a multicountry version of Rogoff's model of the determination of monetary policy in the presence of supply shocks.It is shown that an international transfer system can be designed which creates consensus both on the average rate of inflation and the common response to asymmetric shocks to the participating economies.We conjecture that this kind of transfer mechanisms, institutionalized or informal, supporting joint decisions tend to evolve in contexts where there is strong aversion of disagreement.Monetary policy is arguably such a context, because frequent disagreement within the decision-making body could be harmful to credibility. The transfer system capable of supporting consensus on monetary policy can be based on activity-related, automatic subsidies for countries which would individually prefer lower inflation rates, and activity-related taxes for countries which would prefer higher inflation in absence of the transfer system. It turns out that the common monetary policy created by unanimous decisions under the supporting transfer mechanism can be characterized as a weighted average of the national "stand-alone" inflation rates, i.e. the rates which would prevail without the monetary union.The weights of the countries are not related to the sizes of the national economies, but rather to the national attitudes towards inflation and transfer income.Countries with a low stand-alone rate of inflation get a large weight in the determination of the common monetary policy, as do the countries which have a relatively low marginal valuation of international transfer income.
URN:NBN:fi:bof-20140807463
Keywords: 330; Positive inflation theory; monetary union; monetary policy